Layer-by-Layer Films with CoFe2O4Nanocrystals and Graphene Oxide as a Sensitive Interface in Capacitive Field-Effect Devices - Morais, Paulo V. [UNESP]; Orlandi, Marcelo O. [UNESP]; Schöning, Michael J.; Siqueira, José R. (American Chemical Society (ACS), 2022)
Sensor devices have proved to be a promising technology for portable microelectronic systems for biomedical and environmental applications. Depending on the target analyte and/or the sensor platform chosen, the study of (nano)materials and their ideal incorporation in the device as a receptor layer have great importance for developing sensing units with enhanced properties and performance. Here, we employed the layer-by-layer (LbL) technique to fabricate nanostructured films as sensing units for detecting H2O2 and heavy metal ions (Cd2+ and Cu2+). The LbL film was deposited on electrolyte-insulator-semiconductor (EIS) field-effect devices, combining CoFe2O4 nanocrystals embedded into polyallylamine hydrochloride (PAH) and graphene oxide (GO) as a PAH-CoFe2O4/GO structure. Scanning electron microscopy revealed a LbL film morphology with high surface area presenting heterogeneous clusters of nanocrystals covered by a homogeneous coating of GO. The electrochemical characterization to monitor the film growth and the sensing properties for detecting H2O2 and Cd2+ and Cu2+ ions was carried out by capacitance-voltage (C/V) and constant-capacitance (ConCap) measurements. The results demonstrated catalytic features in detection experiments for an optimized EIS-LbL sensor containing a 6-bilayer PAH-CoFe2O4/GO LbL film. This sensor system was sensitive for all analytes and exhibited a low limit of detection of ca. 314.3 µM for H2O2 and 0.54 and 0.47 µM for Cd2+ and Cu2+ ions, respectively. These findings prove the relevance of incorporating nanostructured films as a receptor layer to enhance sensing properties and may envisage a proof-of-concept field-effect sensor system for environmental applications.
Keywords: CoFe2O4nanocrystals; EIS sensors; field-effect devices; graphene oxide; layer-by-layer technique; nanostructured films